Physiological basis behind ergogenic effects of anabolic androgens. (15th March 2018) - Cheung, Ada S.; Grossmann, Mathis
Abstract: Anabolic androgenic steroids (AAS) are widely abused by the sporting community. Demonstrating performance enhancing effects of AAS in rigorous scientific studies is fraught with difficulty. In controlled studies, AAS have consistently been reported to increase muscle mass and strength. The clinical evidence that these anabolic effects are independent of, and additive to exercise are supported by preclinical studies suggesting that AAS and exercise affect muscle by overlapping, yet distinct mechanisms. AAS may also improve performance by their actions on other organ systems, such as the vasculature, and the erythropoietic and central nervous system, although this evidence is less strong. While most of the actions of AAS are thought to be mediated via classical androgen receptor-mediated genomic signalling, AAS may also produce rapid effects via non-genomic mechanisms. Highlights: Anabolic androgenic steroids (AAS) are widely abused, despite adverse effects. AAS increase muscle strength independent of endogenous testosterone levels or age. AAS have effects on the vasculature, erythropoiesis and the central nervous system. AAS act by classical androgen receptor mediated and by rapid non-genomic effects.